2017
DOI: 10.3390/en10040491
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analyses of a Flat Plate Photovoltaic/Thermal Solar Collector

Abstract: This paper presents a one-dimensional finite-volume model of an unglazed photovoltaic/thermal (PVT) solar collector. The unit consists of a conventional solar photovoltaic (PV) collector coupled with a suitable heat exchanger. In particular, the collector includes a roll bond heat exchanger and it is not equipped with back and frame insulation. The system is discretized along the flow direction (longitudinal) of the cogenerative collector. For each finite-volume element of the discretized computational domain,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The target building had an air-type BIPVT collector installed on the southern side of the building, and had been expanded from a four-story building to a five-story building. The floor area of the enlarged building was 768.02 m 2 , mainly used as classrooms. An electric heat pump (EHP) and HRV were combined with the air conditioning system, and the operation schedule of the system was from Monday to Friday from 9:00 a.m. to 4:00 p.m. (Figures 1 and 2).…”
Section: Demonstration Sitementioning
confidence: 99%
“…The target building had an air-type BIPVT collector installed on the southern side of the building, and had been expanded from a four-story building to a five-story building. The floor area of the enlarged building was 768.02 m 2 , mainly used as classrooms. An electric heat pump (EHP) and HRV were combined with the air conditioning system, and the operation schedule of the system was from Monday to Friday from 9:00 a.m. to 4:00 p.m. (Figures 1 and 2).…”
Section: Demonstration Sitementioning
confidence: 99%
“…The test results showed that the north-facing room had an average temperature over 17 • C while the south-facing room was over 20 • C, which illustrated that a good heating effect was achieved. Although a relatively high system COP was shown with a good heating effect for the solar heating system under the simultaneous charging and discharging operation mode, further recommendations were proposed for the mass flow rates of the solar collecting cycles and control stagey of the fan coil unit (FCU).in Lhasa is promising, as it can contribute to the improvement in indoor thermal comfort, energy consumption reduction and more environmental friendliness [1][2][3].Solar energy is one of the most promising renewable energy sources since it suitably meets sustainable development objectives and it can be exploited worldwide [4][5][6][7][8][9]. Buker et al [10] reviewed the solar thermal applications in buildings, addressed the important issues related to architectural barriers, system design and installation and revealed the trend of solar thermal technologies required in the future.…”
mentioning
confidence: 99%
“…Solar energy is one of the most promising renewable energy sources since it suitably meets sustainable development objectives and it can be exploited worldwide [4][5][6][7][8][9]. Buker et al [10] reviewed the solar thermal applications in buildings, addressed the important issues related to architectural barriers, system design and installation and revealed the trend of solar thermal technologies required in the future.…”
mentioning
confidence: 99%
“…Several cooling techniques have been implemented to reduce PV module operating temperature and the consequent efficiency losses [1,9,10]. Nevertheless, in most cases, their implementation…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics have led many countries to pay attention on the design policies, strategies, and technology for its use [1][2][3][4]. In this context, photovoltaic (PV) systems are one of the most mature solar technologies, and it is constantly increasing its competitiveness and decreasing its production costs [5].…”
Section: Introductionmentioning
confidence: 99%